Evaluation of self-report screening measures in the detection of depressive and anxiety disorders among children and adolescents with systemic lupus erythematosus. (July 2021) - Quilter, Michelle; Hiraki, Linda; Knight, Andrea M; Couture, Julie; Levy, Deborah; Silverman, Earl D; Danguecan, Ashley N; Ng, Lawrence; Dominguez, Daniela; Cost, Katherine T; Neufeld, Kate M; Schachter, Reva; et al.
Background: There are no validated screening measures for depressive or anxiety disorders in childhood Systemic Lupus Erythematosus (cSLE). We investigated cross-sectionally (1) the prevalence of depressive and anxiety disorder in cSLE. (2) the validity of the Centre for Epidemiologic Studies Depression Scale for Children (CES-DC) and the Screen for Childhood Anxiety and Related Disorders (SCARED) measures in identifyingthese disorders. Methods: Participants 8-18 years with cSLE/incipient cSLE completed CES-DC, SCARED, and Quality OfMy Life (QOML) measures. Parents completed the SCARED-Parent measure. Diagnosis was by gold-standard psychiatric interview and determined prevalence of psychiatric disorder. Receiver Operating Characteristics Area under the Curve (ROCAUC) evaluated screening measure diagnostic performance. Results: Ofseventy-two parent-child dyads, 56 interviews were completed. Mean screen scores were: CES-DC = 15 (range 1-49, SD 12), SCARED-C = 22 (range 2-61, SD 14), SCARED-P = 13 (range 0-36, SD 8). Depressive disorder screen positivity (CES-DC ≥ 15) was 35% (vs. prevalence 5%). Anxiety disorder screen positivity (SCARED ≥ 25) was 39% (vs. prevalence 16%). CES-DC ROCAUC = 0.98 and SCARED-C ROCAUC = 0.7 (cut-points 38 and 32 respectively). Conclusions: Diagnostic thresholds for depressive and anxiety disorderscreening measures are high for both CES-DC and SCARED-C in cSLE. Brief focused interview should follow to determine whether psychiatric evaluation is warranted.